A CONVERSATION ANALYSIS OF PREFERENCE ORGANIZATION IN BRAVE MOVIE - Rosyida Ekawati (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
This study is aimed to explain the feature and strategy responses of preference organization used by the main character in Brave movie. In analyzing the data, it was used Levinson’s theory (1983) for the features and Schegloff’s theory (2007) for strategy responses of preference organization that found in the movie. It is a descriptive qualitative research. The data of this study are in the forms of words, phrases, and sentences that contain the features and strategies of preference organization and explained descriptively. Numbering was only used to simply classify the categories. The result showed that the features and accuracy responses of preference organization in Brave movie contain preference organizations of agreements, expected answers, and denial. For dispreferred response, there were refusals, disagreements, and unexpected answers. Meanwhile, the strategies response of preference organization consists of preferred responses in simple and no delay way and elaboration. For dispreferred responses there are mitigations, elaborations, default, and  positioning